A study of Malaysian accounting education in higher-learning institutions: Is Malaysia preparing undergraduates for a tsunami of fraud? - Ong, Derek Lai Teik *; Al-Mashoor, Sharifah Ameera *; Siew, Weng Chung *; Ng, Qing Song * (2013)
The current syllabus lack sufficiency of fraud education in areas of auditing, fraud examination and forensic accounting in the current accounting curriculum. This paper seeks to analyze the relationship between final year accouting students’ perceived coverage of fraud education and the overall sufficiency of the three areas in higher-learning institutions. Learning objectives were used to determine the sufficiency of fraud education in current accounting curriculum and a brief comparison between different higher learning institutions in Malaysia, students with and without internship experience, and test of ethical conduct was performed. Findings include insufficient coverage in the areas of fraud examination and forensic accounting but not auditing and that the students’ perceived coverage of fraud education depends on the sufficiency of fraud examination and forensic accounting areas. The paper only tested the perception aspect of students and results may differ depending on student’s aptitude in learning. This study provides valuable input to redesigning the current accounting curriculum to expose students to fraud-based learning environment and also incorporating forensic accounting courses. It seeks to regain society’s confidence in the accounting profession through improved fraud detection. The research will add value to the accounting education offered to undergraduates as very little prior research has been done to provide insights in students’ (end-user) perception of fraud education.